Sintering schedule for near-net shapping of mechanical components formed through warm compaction route - Rahman M.M.; Nor S.S.M.; Ariffin A.K. (Penerbit UTM Press, 2023)
This paper presents the characterization of solid state sintering schedule for the production of near-net shape mechanical components through warm compaction route. A lab-scale warm forming rig was designed and fabricated which enabled the generation of green compacts at elevated temperature. The feedstock from iron powder ASC 100.29 was prepared by mechanically mixing the powder with 0.4wt% zinc stearate for 30 minutes. The feedstock was formed at 180 to generate green compacts. The defect-free green compacts were subsequently sintered in an inert gas fired sintering furnace for different sintering schedules. The sintered products were characterized through mechanical testing and microstructure evaluation. The result revealed that the mechanical properties and microstructures of sintered products are affected by sintering parameters. Results shown that part sintered at 1000C, 10C/min heating rate for 60 minutes give the highest bending strength of 630 MPa and relative density of 0.869 g cm-3. It also exhibited acceptable dimensional changes which is below 1%. It can observed by micrograph part at sintering temperature of 1000, neck formation is also observed and more metal-metal bonding is visible. From this study, the suitable sintering parameters are identified for the production of near-net shape yet high quality mechanical component. 2012 Penerbit UTM Press.